Conditions for enhanced performance of segmented thermoelectrics under load. (18th July 2017) - Angst, Sebastian; Wolf, Dietrich E
Abstract: The Onsager-de Groot-Callen transport theory is used to investigate the performance of double segmented thermoelectrics as generators. We show that such an inhomogeneous device usually performs worse than predicted by the effective transport coefficients. This is caused by the difference of the open circuit Seebeck voltage and the Seebeck voltage under operating conditions. The electrical current and the related interface Peltier effect cause a self-organization of the temperature profile such that the temperature drop across the material with the higher absolute Seebeck coefficient is reduced. However, including Joule heating we derive conditions for the opposite effect resulting in an enhanced power.